Performance assessment of Krishna Western Delta using remote sensing - a case study - Prasad, P. R. K., author; Jacobs, C., author; Rao, G. Subba, author; Srinivas, D., author; Babu, A. V. Suresh, author; Boonstra, J., author; Satyanarayana, T. V., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2012)
The Krishna delta irrigation system, one of the earliest major irrigation projects in southern India was designed by Sir Arthur Cotton during in the middle of 19th century on river Krishna near Vijayawada. The project irrigates an ayacut of 5.14 lakh hectares covering West Godavari, Krishna, Guntur and Prakasam districts of Andhra Pradesh. Using multi-date satellite data of Krishna Western Delta (KWD), flow information, crop cutting experiment (CCE) plot data of the State Department of Agriculture (SDA) and AP Water Management (APWAM) Project obtained during kharif 2005-06, performance indicators were computed and performance of irrigation system was assessed. Paddy was the major crop gown in KWD. Hence paddy yield model was developed using ground obtained CCE plot yield data and satellite derived normalized difference vegetative index (NDVI). Very good correlation (r = 0.7) was obtained between these parameters. Hence, it was extrapolated to the entire KWD belt. The average yield of KWD derived based on NDVI observations was closely matched with the yield data of APWAM and SDA. Highest efficiency (85%) was obtained in high-level canal command. The lower efficiency obtained in Kommamur was due to poor condition of the canal, high conveyance losses and release of excess rain water in to the sea through the canal. The productivity of water was varying from 0.7 to 1.0 kg m-3 across KWD except in Kommamur which had only 0.5 kg m-3. The information on nature, extent and distribution of salt affected soils and waterlogged areas in KWD was generated based on visual interpretation of FCC imageries obtained from space-borne remote sensing satellites. It was computed that about 18,102 and 4,675 hectares of area was salt affected and waterlogged, respectively.
Irrigated agriculture responds to water use challenges
Performance assessment using remote sensing
Presented at Irrigated agriculture responds to water use challenges - strategies for success: USCID water management conference held on April 3-6, 2012 in Austin, Texas.